2019
DOI: 10.1002/solr.201900079
|View full text |Cite
|
Sign up to set email alerts
|

Organic Solar Cells Based on High Hole Mobility Conjugated Polymer and Nonfullerene Acceptor with Comparable Bandgaps and Suitable Energy Level Offsets Showing Significant Suppression of JscVoc Trade‐Off

Abstract: Herein, a high‐mobility polymer (Si25) pairing a nonfullerene acceptor (O‐IDTBR) is introduced to construct active layers of organic solar cells (OSCs). The OSCs based on Si25 and O‐IDTBR with comparable bandgaps of 1.61 eV show high open‐circuit voltage (Voc) of 1.03 V. Suitable energy level offsets between the donor and acceptor as well as sufficient photon absorbance by a 400 nm thick active layer afford a notable short‐circuit current (Jsc) of 21.11 mA cm−2, indicating a significantly suppressed trade‐off … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 112 publications
(129 reference statements)
1
18
0
Order By: Relevance
“…This can be explained by the enlarged conjugation and profitable interfacial modification, and a higher mobility which is one of main causes of a higher J sc . [44,45] Taking the hole mobility into account, the balance between μ e /μ h of HBC-S has been 0.96 while the HBC-H obtained 0.62, which possibly well supported the such a high FF of the HBC-Sbased devices. In addition, the ability of exciton dissociation also reflects the quality of the interfaces.…”
Section: Improvement Of J Sc and Ff Related To Carrier Transportmentioning
confidence: 61%
“…This can be explained by the enlarged conjugation and profitable interfacial modification, and a higher mobility which is one of main causes of a higher J sc . [44,45] Taking the hole mobility into account, the balance between μ e /μ h of HBC-S has been 0.96 while the HBC-H obtained 0.62, which possibly well supported the such a high FF of the HBC-Sbased devices. In addition, the ability of exciton dissociation also reflects the quality of the interfaces.…”
Section: Improvement Of J Sc and Ff Related To Carrier Transportmentioning
confidence: 61%
“…These devices are the result of careful and delicate optimization of the active layer morphology. From this point of view, IDTBR (a2) is again one of the more robust acceptors, with PCE as high as 8.1% for 1010 nm thick devices [78]. IDIC-type acceptors provide devices with 8.5% PCE at a 530 nm thickness (for comparison, the PCE at 105 nm is 12.2%) [79], while in the case of the ITIC-type acceptor, a device with 8.9% at 500 nm has been reported (12.7% at 141 nm) [80].…”
Section: Industrial Considerations and Scalability Of Nfasmentioning
confidence: 97%
“…Moreover, by introducing a siloxane‐terminated side chain, the copolymer PFBT4T‐C5Si‐25% obtained PCEs of 10.95% at a film thickness of 380 nm and 11.09% at 420 nm in fullerene systems, and a PCE of 11.5% at 400‐nm thickness was also achieved when blended with O‐IDTBR. The introduction of siloxane chain enhanced the face‐on orientation and resulted in favorable three‐dimensional hole transport in thick junctions, such that the FF becomes stabilized at 74% as the J SC slightly increases with greater film thickness 56,57 . Further investigation revealed that with a higher molecular weight, PFBT4T‐C5Si‐25%:IEICO‐4F devices showed an improved absorption, uniform morphology, and enhanced charge mobility, which resulted in a J SC improving from 19.7 to 26.8 mA cm − 2 at an optimal thickness of 320 nm (Figure 5C).…”
Section: Molecular Design Strategies For Thickness‐insensitive Materialsmentioning
confidence: 99%
“…The introduction of siloxane chain enhanced the face-on orientation and resulted in favorable three-dimensional hole transport in thick junctions, such that the FF becomes stabilized at 74% as the J SC slightly increases with greater film thickness. 56,57 Further investigation revealed that with a higher molecular weight, PFBT4T-C5Si-25%:IEICO-4F devices showed an improved absorption, uniform morphology, and enhanced charge mobility, which resulted in a J SC improv-ing from 19.7 to 26.8 mA cm −2 at an optimal thickness of 320 nm ( Figure 5C). 58 Based on the ffBT and NT systems, Yan et al studied the influence of temperature-dependent behavior on morphology control, and reported PCEs ranging from 9.5 to 10.5% at a film thickness of 300 nm.…”
Section: 6-difluorobenzothiadiazole-based Polymersmentioning
confidence: 99%